Spatial analysis of granting of social welfare benefits to people with gastrointestinal Chagas disease in Brazil, 2004-2016: a time series study - Jean Ezequiel Limongi; Keile Aparecida Resende Santos; Izabela Lima Perissato; Rivaldo Mauro Faria (Epidemiologia e Serviços de Saúde)
Abstract Objective To analyze patterns of spatial association in the granting of social welfare benefits to individuals with gastrointestinal Chagas disease in Brazil in the period 2004-2016. Methods This was a time series analysis, using secondary data provided by the Ministry of Labor and Employment. The analyses were performed using global and local Moran indices spatial autocorrelation techniques. Results In all, 4,661 benefits were granted, mainly to residents of urban areas (n=3,285, 70.5%), males (n=2,819, 60.5%) and with average age of 49.5±9.3 years. The main benefits granted were social welfare due to temporary incapacity (n=3,754, 80.5%), retirement due to permanent incapacity (n=581, 12.5%) and assistance support for people with disabilities (n=320, 6.9%). The most significant values found for the global Moran index were for the variables “benefits to individuals aged ≥60 years old” (0.673; p-value 0.001) and “benefits granted in urban areas” (0.666; p-value 0.001). Health macro-regions in the states of Minas Gerais, Goiás and Bahia stood out, forming high-high clusters in the local Moran index analysis when benefit granting was analyzed according to sex, area of residence, type of benefit granted and age. Conclusion The concentration of benefit granting in Minas Gerais, Goiás and Bahia is a result of the intense transmission of the disease in these areas in past decades. Longitudinal monitoring of the population chronically affected by Chagas disease, mainly by Primary Care teams, can reduce the impact of the disease on social support and social security.